Teologi Penderitaan dan Pengorbanan dalam Perpektif Kristiani dalam Konteks Pelayanan Tim Medis COVID-19 - Bernardus Ario Tejo Sugiarto (Universitas Katolik Parahyangan, 2022)
This study focuses on suffering and sacrifice, 'there is no sacrifice without suffering', particularly: the suffering and sacrifice of the medical team members in overcoming the Covid-19 pandemic in Indonesia. The objectives of the research are (1) to describe their theological view of the reality of suffering and sacrifice in their ministry and its relation to Christian theology, and (2) to analyze the role of theology in their professional ministry. The author of the research has utilized a mixed-method with data collection carried out using a quantitative (tool: questionnaire) and qualitative approach (tool: video from Youtube channel). The author stipulates doctors, nurses, and midwives who are involved in handling Covid-19 patients at the Santo Yusup Hospital and the Santo Borromeus Hospital in Bandung as respondents. In this study, the author also excerpts statements of doctors, nurses, or midwives from various hospitals in videos uploaded on the Youtube channel as part of the research data. The results of this study are that although it does not reach the meaning of redemption, the Covid-19 medical team who experience disappointment, sadness, and concern view the sacrifices made for the lives of others as precious actions so that they continue to strive to provide the best service. Prayers and good teachings taught in religion evoke their motivation and strength to be faithful in their ministry.